Treatment of hypothyroidism - Małecka, Paulina; Małecka-Kacpura, Justyna; Fabian-Danielewska, Anna (Journal of Education, Health and Sport, 2018)
Hypothyroidism is a deficiency of thyroid hormones or their insufficient activity. The most common cause of this disease is chronic autoimmune thyroiditis (Hashimoto’s disease), iodine deficiency, partial or complete thyroid removal, and some medicines. Congenital hypothyroidism - may be primary or secondary to disorders of the pituitary gland or hypothalamus. The most common symptoms in the newborn are: prolonged jaundice, dry skin, constipation, umbilical hernia, large tongue, hypotonia, hoarseness, large bloated stomach. Hypothyroidism in pregnancy can lead to such complications as: preeclampsia, hypertension in pregnancy, spontaneous abortion, habitual abortion and even fetal death. It is important to recognize hypothyroidism and start treatment as early as possible. In the elderly, intensive treatment of subclinical and clinical hypothyroidism is not recommended. Treatment should be considered for people > 85 years of age with TSH level> 10 mIU/l, the usual indication for treatment are clinical symptoms.